Estudo da erosão hídrica laminar do solo da bacia hidrográfica do córrego São José, em Francisco Beltrão (PR), utilizando técnicas de geoprocessamento - Vansan, Ana Paula (2017)
The expansion of the use of agricultural areas without the implementation of measures that reduce the impact caused by the exposure of the soil to the elements, negatively altering the hydrological and sedimentological regimes in the basins. The objective of this study was to evaluate the soil erosion of the soil by means of the Revised Soil Loss Universal Equation (RUSLE) in the São José stream basin, located in the municipality of Francisco Beltrão (PR). The average annual soil loss (A) was determined through RUSLE for the years 2000, 2005, 2009, 2015 and 2017 using geoprocessing techniques with ArcGis 10.0 software. Rainfall erosivity (R) was determined using rainfall data from 1974 to 2016. The soil erodibility factor (K) was obtained through the analysis of soil samples collected on the spot. The topographic factor (LS) was estimated by means of the altimetric and hydrographic data of the basin. The CBERS 4 (2017 and 2015), CBERS 2B (2009), CBERS 2 (2005) and Landsat 5 (2000) satellites were used to determine the land use and management factor (C), using multitemporal characterization of land use and occupation. A value of 1 was attributed to the soil conservation practices (P), due to the lack of conservation practices implemented for exposed soil areas, 0.01 for tree vegetation areas, and 0.5 for pasture and agriculture because they are no-tillage areas. The natural erosion potential (NEP) was determined by multiplying the R, K and LS factors. The soil loss estimation (A) was determined by the multiplication of the NEP by the factors C and P The low soil loss class, ranging from 0 to 10 t.ha-1.year-1, is the predominant in the basin, corresponding from 38.85% to 55.35% of the total area, characterizing it as being of low susceptibility to erosion. It can be observed that the natural potential of erosion (PNE) has little influence on the susceptibility to erosion in relation to the factors of use and management and conservation practices of the soil, since even possessing a natural potential of very strong erosion, it has soil loss predominantly classified as low.